2012
DOI: 10.4103/0974-8490.102263
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the hepatoprotection to heavy metals of Zingiber officinale

Abstract: Context:Zingiber officinale (Zingiberaceae) is a herb used for culinary and therapeutic purposes due to its anti-inflammatory and antioxidant potentials.Objectives:We examined its protective ability against mercury (Hg), lead (Pb) and cadmium (Cd) accumulation in the liver.Materials & Methods:Ground Zingiber officinale (7%, w/w of feed) was administered to rats either at the same time with the exposure ofheavy metals (group 2), a week after exposure to heavy metals (group 3) or given a week before heavy metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The unexpected patterns observed in the kinetics of elimination and uptake of these chemicals/metals have been reported even with continuous exposures and is not due to experimental or analytical errors. [2224] Nutrient substances like PO are reported to provide a great deal of antioxidants which can affect the toxico-dynamics and bioavailability of heavy metals following exposure. [2330] PO is able to reduce the bioavailability of these metals by possibly complexing and enhancing its elimination/excretion from the tissues like some other nutrient substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unexpected patterns observed in the kinetics of elimination and uptake of these chemicals/metals have been reported even with continuous exposures and is not due to experimental or analytical errors. [2224] Nutrient substances like PO are reported to provide a great deal of antioxidants which can affect the toxico-dynamics and bioavailability of heavy metals following exposure. [2330] PO is able to reduce the bioavailability of these metals by possibly complexing and enhancing its elimination/excretion from the tissues like some other nutrient substances.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of the chosen metals were obtained through preliminary studies and review of literature. [2324] Care was taken to choose a concentration that will assure the survival of the animals throughout the period of study.…”
Section: Methodsmentioning
confidence: 99%
“…According to Ried and Fakler (2014), garlic-derived polysulfides stimulate the production of the vascular gasotransmitter hydrogen sulfide and enhance the regulation of endothelial nitric oxide, which induce smooth muscle cell relaxation, vasodilation, and blood pressure reduction. Moreover, Nwokocha et al (2011) showed that garlic extract caused a reduction in blood pressure and heart rates in hypertensive rat models. (Nawash et al, 2013).…”
Section: Fidelity Level (Fl)mentioning
confidence: 98%
“…[9101112] Our results showed that the additives used affected the accumulation levels of lead in the liver. Some of them significantly reduced the accumulation, while others had no effect or, interestingly, increased its accumulation.…”
Section: Discussionmentioning
confidence: 94%